TEACHING LEARNING PROCESS ON SPEAKING SKILL AT ENGLISHDEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA: A MICRO ETNOGRAPHY - MUTMAINAH, SITI (2011)
This research aims at describing the teaching learning process on speaking skill at second semester English Department of Muhammadiyah University of Surakarta. It is conducted to describe the objective learning, the material, methods of teaching, classroom techniques, teacher roles, student roles, the strenghts and weaknesses of the English Department. In this research the data are derived from event, information and document. There are three techniques in collecting the data namely: interview, observation, and document. The data achieved from information related to the teaching learning process on speaking 2, in form of the field note, interview scripts and document. Teaching learning process on speaking skill at English Department of Muhammadiyah Universtity of Surakarta, the result are 1) The lecturer used eclectic methods, the lecturer combined two methods, namely Communicative Language Teaching (CLT) and Audiolingual method (ALM), 2) The procedure in speaking 2 are review, explanation, practice and feedback, 3) The lecturer used role-play and describing people in classroom techniques, 4) teacher role are as manager, facilitator, counseler, instructor, motivator, and evaluator, 5) learner role are as listener and performance, 6) strength in teaching speaking 2 are students are more active in the class, students are more communicative in the class and the students are more motivated in learning. The weaknesses are they felt nervous when the lecturer asked them to come forward one by one in front of the class, The students are difficult to arrange the sentence in the class, The lecturer is difficult to evaluate the students performance one by one.